APLIKASI METODE RAIMONDI DAN BOYD PADA PERBANDINGAN ANALISIS PERFORMANSI JOURNAL BEARING LOKOMOTIF YANG MENGALAMI BEBAN IMPAK - Budiwantoro, Bagus; Firmansyah, Ridha; Puja, IGN Wiratmaja (Mesin, 2006)
Axle Lining is a type of journal bearing at wheel driver shaft in which makes locomotive traction motor possible to be supported on the mover shaft. According to hydrodynamic lubrication theory, journal bearing is designed to work under hydrodynamic lubrication condition. Film layer between journal and bearing surfaces can give less contact between those surfaces. When the bearing is working, all performance parameters such as minimum film thickness, eccentricity ratio, bearing friction coefficient, lubricant flow, maximum lubricant pressure, temperature rise of lubricant, have to be achieved thus the bearing can reach the desired life and performances. Impact load, which works to bearing, is one important factor to be noticed because it can affect bearing performance comprehensively. Using numerical Raimondi and Boyd method which developed in form of computer program, the process to determine journal bearing performance calculation can be easier and give more accurate result. The application of this method for the calculation performance import and local product show that imported journal bearing work under hydrodynamic condition for low value of impact load up to 1500 lbf (6,68 kN). Local product work under elastohydrodynamic condition for low value of impact load up to 1000 lbf (4,45 kN). Critical impact load is 1500 lbf (6,68kN) for both product which calculated using Trumpler criteria .